PERANCANGAN ALAT UJI PENETRASI PADA HELM DENGAN STANDAR SNI 1811-2007 SISTEM SEMI OTOMATIS - Iqbal Romadhan, Muhammad (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Helmet is a head protection device, especially for motorized vehicle drivers in the form of a head covering that protects the head in the event of a collision. Helmets marked with SNI are helmets that have passed the tests required by SNI 1811-2007 and have received the SNI mark. There are many types of helmets on the market that have passed standardized tests and one of them is the penetration test. Penetration test with a conical metal nail for testing. The indenter falls from a maximum height of 1.6 m, if the helmet is see-through, it means the helmet has failed the standard test, and vice versa. Therefore the penetration test tool is a tool design made on a standard SNI 1811-2007 helmet with safe operation. As well as determining the function of the tool parts and the simulation results of this penetration test tool running properly and correctly. The results of the penetration test design that have been carried out are that designing the drawing of the penetration test tool is in accordance with the SNI 1811-2007 standard which is where the height from the tip of the indenter to the test material is 1.6 meters and the specifications of the indenter with a conical indenter tip 60°, metal hardness 40-50 Rockwell -C, and the overall weight is 3 kg. And Design a penetration test tool that has been optimized easily and simply as well as the simulation results of a safe penetration test as needed.